Design of a Temperature Control and Object Motion Detection System in the Server Room Using IOT-Based Wemos D1 - Rizky Hidayat; Novriyenni Novriyenni; Siswan Syahputra (Yayasan Kita Menulis, 2023)
Servers play an important role in managing information and managing network traffic within an agency. It contains various types of network devices that must be kept on every day to provide the best service. This leads to the importance of maintaining server presence, such as paying attention to room humidity, regulating temperature and monitoring server room movements to keep it under control. The air temperature in the server room is set within 20 - 25 degrees Celsius with a relative humidity of 40 - 55%. In this context, the concept of the Internet of Things (IoT) emerges as a potential solution by connecting physical objects via the internet. This research designs and builds an IoT-based temperature control and object motion detection system using a DHT22 sensor to measure the temperature in the room and a PIR sensor to detect human movement. Hardware components such as Wemos D1, Buzzer, Relay 2 channel 5v, and others are used to control the system via a smartphone. The software used includes the Arduino IDE. This system aims to monitor and control room temperature and object movement detection systems intelligently, prevent overheating, reduce the risk of loss and combine the advantages of IoT technology to create a temperature control and motion detection system that is responsive to room temperature and the movement of objects in the room.